STRATEGI PENGEMBANGAN HUTAN KEMASYARAKATAN DENGAN POLA AGROFORESTRY DI DESA AMAL KECAMATAN SINDUE KABUPATEN DONGGALA - Syahrizal, Syahrizal (JSTT, 2015)
Development of community forest with agroforestry system is in compliance with forestry implementation, by considering aspiration and participation of community. The study was conducted by using survey method at study site and closed interview with key informans, i,e: farmer, community leader, NGO, decision maker in the village. The result of study showed that community forest might be have high potency to be developed based on the large area of degradated by planting local trees in agroforestry system. Therefore, forest should be sustained by planty local trees either in natural forest or in plantation by growing local trees in agroforestry system might increase the community income.